1783 Mass. Acts 37, § 2 - (:unkn) unknown (General Publisher, 1783)
Prohibited the possession of any “fire arms,” and among other devices, loaded with any gun powder. Punishable by forfeiture and sale at public auction.
--
Keywords: POSSESSION